1971
DOI: 10.2134/agronj1971.00021962006300010039x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Accumulation in Vegetables. I. Spinach Grown in Upland Soils1

Abstract: The nitrate concentrations in spinach (Spinacia oleracea L.) blades and petioles were determined for different sources and times of application of N fertilizers to a Honeoye fine sandy loam and a Lima silt loam to determine the effect of N fertilization on the concentration of nitrates in the plant parts used for consumption for food. Nitrate concentrations were determined potentiometrically, using a nitrate‐selective ion electrode, on plant samples taken at time intervals after N fertilization and at harvest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

1976
1976
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 4 publications
1
20
0
3
Order By: Relevance
“…Some authors reported that it can also reduce NO 3 accumulation in comparison with NO 3 fertilizers when side-dressed to growing crop (Barker et al, 1971). However, in most soils NH 4 applied is rapidly nitrified.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported that it can also reduce NO 3 accumulation in comparison with NO 3 fertilizers when side-dressed to growing crop (Barker et al, 1971). However, in most soils NH 4 applied is rapidly nitrified.…”
Section: Introductionmentioning
confidence: 99%
“…The high levels of nitrite observed in spinach treated with DHA-S was probably related to its injurious effect on spinach leaf tissue. Sodium dehydroacetate, by impairing the integrity of leaf tissue, might facilitate the penetration of bacteria into nitrate-rich locations such as the veins (Peck et al, 1974) and the petioles (Barker et al, 1971;Peck et al, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, urea can be easily hydrolyzed to NH4 +, whose uptake by plants may result in a dramatic pH decrease in the nutrient solution (Luo et al 1993). Secondly, the presence of NH4-N instead of N0 3 -N in the nutrient solution may interfere with the uptake of nutrients, particularly cations (Barber 1984). Another problem is that plants grown with urea without Ni supplementation accumulate urea and show chlorosis or develop necrosis of the leaf edges (Gerendas and Settelmacher 1997b).…”
Section: Discussionmentioning
confidence: 99%